2020
DOI: 10.3390/microorganisms8060811
|View full text |Cite
|
Sign up to set email alerts
|

Age and Species of Eucalyptus Plantations Affect Soil Microbial Biomass and Enzymatic Activities

Abstract: Soil microorganisms and extracellular enzymes play important roles in soil nutrient cycling. Currently, China has the second-largest area of eucalyptus plantations in the world. Information on the effects of eucalyptus age and species of trees on soil microbial biomass and enzyme activities, however, is limited. In this paper, the soil microbial biomass and enzyme activities were studied in eucalyptus plantations with different ages (1 and 5+ years) and species of trees (E. urophylla×E. grandis, E. camaldulens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 71 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…Soil microorganisms play a great role in the biogeochemical process of wetlands (Sousa et al, 2015) and can provide nutrients for the development and function of soil and plants (Li et al, 2015;Xu et al, 2020). Soil microbial properties such as microbial biomass and enzyme activities are essential components of wetlands (Xiao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil microorganisms play a great role in the biogeochemical process of wetlands (Sousa et al, 2015) and can provide nutrients for the development and function of soil and plants (Li et al, 2015;Xu et al, 2020). Soil microbial properties such as microbial biomass and enzyme activities are essential components of wetlands (Xiao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Soil microbial properties can be affected by soil properties such as soil C and N content, pH, moisture content, bulk density, and nutrients (Kotroczó et al, 2014;Baddam et al, 2016;Wang et al, 2019). They can also be affected by plant properties such as plant biomass, species composition, and age (Yuan and Yue, 2012;Xu et al, 2020). Moreover, soil microbial properties can also be influenced by land use/cover change (Raiesi and Beheshti, 2014;Feng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…NAG is involved in the decomposition of chitin and fungal mycelium ( 39 ), and sulfatase is involved in the hydrolyzation of sulfate esters ( 40 ). Previous studies have indicated that the activities of both enzymes were correlated positively with soil microbial biomass ( 38 , 41 ). The NAG and sulfatase activities being significantly higher in the PLF may result from the increased fungal biomass, which can also explain the significantly increased fungal α-diversity and richness in the PLF site.…”
Section: Discussionmentioning
confidence: 91%
“…The variation in tree species in the three forest types could be the key contributor to the observation. The physiochemical properties of soil (e.g., soil pH and nutrient availability) can be altered by tree species ( 41 ), which are important regulators affecting soil microbial communities ( 10 , 11 ). Soil pH and soil C and N content also significantly differed among the three forests during the succession in our study (see Table S1 in the supplemental material).…”
Section: Discussionmentioning
confidence: 99%
“…Within the scope of agricultural microbiology, Xu et al [ 15 ] evaluated the effects of eucalyptus age and species on the soil microbial biomass and enzyme activities. In addition, two studies, performed by the same group, intended to explore the diversity and characteristics of rumen bacterial community [ 16 ], the digestive ability and physiological characteristics of finishing cattle after dietary changes [ 17 ].…”
mentioning
confidence: 99%